After The QALY: Training for a New Start Paradigm in Health Technology Assessment - Paul C Langley; Elliott M Sogol (University of Minnesota Libraries Publishing, 2023)
INTRODUCTION There is a need for a new paradigm to support health technology assessment (HTA). A recent evaluation of the status of the standards for therapy assessment in HTA concluded that practitioners were locked into a meme, rather than a paradigm. A meme that denied a commitment to the evolution of objective knowledge, the discovery of provisional new facts, in favor of the creation of approximate information through a commitment to construction of assumption driven simulations that support non-empirically evaluable claims for cost-effectiveness. This commitment in health technology assessment to the construct of assumption driven modeled simulations to create lifetime imaginary claims for comparative cost-effectiveness is being increasingly recognized as an analytical dead end. Introduced as a framework for creating non-evaluable approximate modeled information it lacks any commitment to the standards of normal science or the requirements of Rasch or modern measurement theory; none of the claims that are made for product pricing and access meet standards for credibility, empirical evaluation or replication[i]. Based on the mathematically impossible quality adjusted life year (QALY), there is a pressing need for a new start in health technology assessment to ensure that the standards for product assessment meet those of the physical and more mature social sciences such as education, psychology and economics. There is a recognized need to move from supporting non-evaluable modeled claims to inform formulary decisions to a framework for HTA endeavors to support the standards of normal science and those of fundamental measurement. Our focus must be on meeting the standards of the physical sciences and the advanced social sciences. The adoption of a new framework will not be easy. It is not an option but an imperative if HTA is to retain any attempt to be taken seriously in health care decisions. To achieve this a commitment to minimum standards in HTA are essential and where pharmacy teaching programs can play a key part.